The assassins' gate America in Iraq - Packer, George 1960- (New York Farrar, Straus and Giroux, 2005)
This book recounts how the United States set about changing the history of the Middle East and became ensnared in a guerrilla war in Iraq. It brings to life the people and ideas that created the Bush administration's war policy and led America to the Assassins' Gate--the main point of entry into the American zone in Baghdad. The consequences of that policy are shown in the author's reporting on the ground in Iraq for The New Yorker. We see up close the struggles of American soldiers and civilians and Iraqis from all backgrounds, thrown together by a war that followed none of the preconceived scripts. The book also describes the war in American life: the ideological battles in Washington, the ordeal of a fallen soldier's family, and the political culture of a country too polarized to realize such a vast and morally complex undertaking.--From publisher description.
Prologue: the assassins' gate -- An unfinished war -- Fevered minds -- Exiles -- Special plans -- Psychological demolition -- The palace -- The captain -- Occupied Iraqis -- Insurgencies -- Civil war? -- Memorial day -- The birth of politics -- Epilogue.
Keywords: Iraq War, 2003-2011.; Iraq War, 2003-2011 -- Occupied territories; Insurgency -- Iraq; Civil war -- Iraq; Americans -- Iraq; Iraq -- Politics and government -- 2003-.; United States -- Politics and government -- 2001-2009.